Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

Chansons de cours-nu-pieds - Miville-Deschênes, Monique (Éditions Triptyque, 2001)

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

L’homosexualité dans la chanson : du bout des lèvres - Perron, Gilles (Québec français, 2001)

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian,; Québécois; anglophone,; francophone,; music,; newspapers,; politics,